2013
DOI: 10.1111/jeb.12168
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for adaptive phenotypic differentiation inBalticSea sticklebacks

Abstract: The evidence for adaptive phenotypic differentiation in mobile marine species remains scarce, partly due to the difficulty of obtaining quantitative genetic data to demonstrate the genetic basis of the observed phenotypic differentiation. Using a combination of phenotypic and molecular genetic approaches, we elucidated the relative roles of natural selection and genetic drift in explaining lateral plate number differentiation in threespine sticklebacks (Gasterosteus aculeatus) across the entire Baltic Sea basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 124 publications
(256 reference statements)
4
52
1
Order By: Relevance
“…Although the possibility of false positives must be taken into account when interpreting outlier tests, it is reassuring that the well-known candidate locus Eda was the most significant outlier. Nevertheless, F ST at this locus was relatively low (0.11); this corresponds to F ST values of 0.12 and 0.10 observed in some previous studies [40, 78], but is considerably lower than differentiation observed in a number of other studies reviewed by Raeymaekers et al [40], with F ST ranging from 0.38 to 0.86. Even though clines at loci and traits were shallow, the fact that there was general concordance between the geographical positions of cline centers also suggests a response to an environmental gradient.…”
Section: Discussionsupporting
confidence: 48%
“…Although the possibility of false positives must be taken into account when interpreting outlier tests, it is reassuring that the well-known candidate locus Eda was the most significant outlier. Nevertheless, F ST at this locus was relatively low (0.11); this corresponds to F ST values of 0.12 and 0.10 observed in some previous studies [40, 78], but is considerably lower than differentiation observed in a number of other studies reviewed by Raeymaekers et al [40], with F ST ranging from 0.38 to 0.86. Even though clines at loci and traits were shallow, the fact that there was general concordance between the geographical positions of cline centers also suggests a response to an environmental gradient.…”
Section: Discussionsupporting
confidence: 48%
“…First, being a conspicuous, variable and easily studied trait, variation in plate numbers has been used as a diagnostic trait in stickleback systematics5960. Second, at least in the three-spined stickleback, the adaptive value of variation in lateral plate numbers is fairly well understood67, and several studies have demonstrated the adaptive nature of temporal6869 and spatial24707172 variation in plate numbers. While the genetic basis of lateral plate number variation in the three-spined stickleback is controlled by a major QTL in the locus close to the Eda -gene, together with several minor QTL2457, different large effect QTL have been identified to control variation in lateral plate numbers in North American nine-spined sticklebacks58.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of phenogeography and phylogeography should contribute to better understanding of functional phenotypic evolution, and then fitness performance within and among lineages (Zamudio, Bell, & Mason, 2016). However, phenogeography—with the noticeable exception of counter‐ and cogradient variation studies (Conover, Duffy, & Hice, 2009; Hice, Duffy, Munch, & Conover, 2012) and few Q ST ‐F ST studies (DeFaveri & Merilä, 2013)—remains largely neglected in marine species. Indeed, while studies regarding changes in quantitative phenotypic differences mediated by trait plasticity and/or genetic processes are obviously present in the literature associated to evolutionary ecology of marine species (Conover et al., 2006; Sanford & Kelly, 2011), most studies concentrated at the molecular level (i.e., gene expression studies, population genetics/genomics) rather than on quantitative biological traits aiming to document the causes of variation of an organism phenotype over a large geographic scale, and their impact on fitness.…”
Section: Introductionmentioning
confidence: 99%